MRI surveillance following treatment of extremity soft tissue sarcoma. Issue 6 (24th December 2013) - Cheney, Matthew D.; Giraud, Christine; Goldberg, Saveli I.; Rosenthal, Daniel I.; Hornicek, Francis J.; Choy, Edwin; Mullen, John T.; Chen, Yen‐Lin; DeLaney, Thomas F.
Abstract Background and Objectives Local recurrence (LR) following limb‐sparing surgery and radiation therapy (RT) for extremity soft tissue sarcoma (STS) is rare. The current study investigates the utility of surveillance nuclear magnetic resonance imaging (MRI) for detection of asymptomatic LRs. Methods The study cohort consisted of 168 adult patients with extremity STS treated with limb‐sparing surgery and RT with curative intent between October 2001 and January 2011. Follow‐up surveillance MRIs and history and physical examinations were performed per the NCCN guidelines with additional MRIs as clinically indicated. The method of LR detection and MRI number and indication were determined. Results After a median follow‐up of 4.7 years (range: 0.6–10.5) 11 (6.5%; 11/168) patients developed LRs. Five hundred two MRIs were obtained, 429 (85.5%; 429/502) for surveillance and 73 (14.5%; 73/502) as clinically indicated. One hundred fourteen patients underwent ≥1 surveillance MRI. The median surveillance MRI interval was 6.4 months (range 1.4–68.9). Surveillance MRI detected an asymptomatic LR in 1 (0.9%; 1/114) patient with a complex reconstruction. Conclusions Surveillance MRI infrequently detects asymptomatic LRs following limb‐sparing surgery and RT for extremity STS and should be limited to patients whose primary tumor sites are not easily assessed by history and physical examination. J. Surg. Oncol. 2014 109:???–???. © 2013 Wiley Periodicals, Inc.